2023
DOI: 10.3389/fmicb.2023.1109550
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the external signals driving the transcriptional regulation of the main genes involved in denitrification in Haloferax mediterranei

Abstract: Haloferax mediterranei is the model microorganism for the study of the nitrogen cycle in haloarchaea. This archaeon not only assimilate N-species such as nitrate, nitrite, or ammonia, but also it can perform denitrification under low oxygen conditions, using nitrate or nitrite as alternative electron acceptors. However, the information currently available on the regulation of this alternative respiration in this kind of microorganism is scarce. Therefore, in this research, the study of haloarchaeal denitrifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Previous studies found a regulatory motif (CGAAYATDKTYG) in the promoter regions of the main denitrification genes and other genes in the H. mediterranei genome, using the bioinformatic tool FIMO ( 21 , 23 , 82 ). These other genes include previously identified accessory proteins and a number of other proteins that have not been formally linked to the denitrification process ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies found a regulatory motif (CGAAYATDKTYG) in the promoter regions of the main denitrification genes and other genes in the H. mediterranei genome, using the bioinformatic tool FIMO ( 21 , 23 , 82 ). These other genes include previously identified accessory proteins and a number of other proteins that have not been formally linked to the denitrification process ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Denitrification-related genes found in the genome of H. mediterranei in a previous study were compared with the transcriptomic analyses of the current study ( 23 ). From that study, a set of 82 promoter regions that shared the regulatory motif CGAAYATDKTYG was used for further analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations